2020
DOI: 10.1080/2162402x.2019.1710389
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the role of FAMIly history of cancer and diagnosis of multiple neoplasms in cancer patients receiving PD-1/PD-L1 checkpoint inhibitors: the multicenter FAMI-L1 study

Abstract: Background: We investigate the role of family history of cancer (FHC) and diagnosis of metachronous and/or synchronous multiple neoplasms (MN), during anti-PD-1/PD-L1 immunotherapy. Design: This was a multicenter retrospective study of advanced cancer patients treated with anti-PD-1/ PD-L1 immunotherapy. FHC was collected in lineal and collateral lines, and patients were categorized as follows: FHC-high (in case of cancer diagnoses in both the lineal and collateral family lines), FHC-low (in case of cancer dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…This is of particular importance to determine whether the influence on clinical outcomes might be driven by associative rather than causative links, especially given the high prevalence of polypharmacy in patients with cancer. 14 Recently, we created a large multicenter, observational study of patients receiving PD-1/PD-L1 checkpoint inhibitors in clinical practice, already subject of several analyzes, [15][16][17][18][19][20] and we now gathered the baseline concomitant medication information for the same population, in order to evaluate their impact on clinical outcomes.…”
Section: Open Accessmentioning
confidence: 99%
“…This is of particular importance to determine whether the influence on clinical outcomes might be driven by associative rather than causative links, especially given the high prevalence of polypharmacy in patients with cancer. 14 Recently, we created a large multicenter, observational study of patients receiving PD-1/PD-L1 checkpoint inhibitors in clinical practice, already subject of several analyzes, [15][16][17][18][19][20] and we now gathered the baseline concomitant medication information for the same population, in order to evaluate their impact on clinical outcomes.…”
Section: Open Accessmentioning
confidence: 99%
“…In the multicenter retrospective study of 211 advanced cancer patients, Cortellini and colleagues also found statistically significant correlation between family history of cancer and ICI response with improved ORR (p = 0.0024), DCR (p = 0.0161), median time to treatment failure (p = 0.0203), and median OS (p-0.0221) [ 28 ]. Expanded analyses of 811 advanced cancer patients upheld family history of cancer as an independent predictor of PFS and OS in multivariable analyses [ 29 ]. Our data supports their assessment that family history of cancer may be a surrogate for known (and yet to be identified) syndromes of inherited cancer susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter retrospective study by Cortellini et al (Cortellini et al, 2018; Cortellini et al, 2020), FHC‐positive patients experienced greater benefit from immune checkpoint inhibitors, suggesting that underlying genetic alterations may lead to changes in immune sensitivity. As incorporating germline genetic testing into medical management has occurred in other tumors, for example, breast, ovarian, and bladder cancer, it may be proved helpful 1 day in OSCC treatment decisions (Nicolosi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%